Clima escolar y tipo de comunicación en estudiantes de educación secundaria de la Institución Educativa N° 601014 República del Perú, Provincia Mariscal Ramón Castilla 2024 - Ruiz Dacosta, Edith Esther (2025)
The purpose of this research was to determine the relationship between school climate and the type of communication in secondary school students of Educational Institution No. 601014 República del Perú, Mariscal Ramon Castilla Province 2024. Opting for a basic type study, with a quantitative approach, non-experimental design, the sample consisted of 80 students to carry out the survey conducted by two questionnaires for data collection. The findings show that the school climate was rated as "good" by 45%, while 23.7% rated it as "bad". Regarding the type of communication, it was rated as "good" by 55%, while 7.5% rated it as "bad". Therefore, it is determined that between the variables there is a direct relationship between the school climate and the type of communication by a coefficient of rho = 0.991 and p = 0.000. Likewise, the relationships dimension presents a coefficient and significance of rho=0.996 and p=0.000; likewise, the self-actualization dimension shows a coefficient and significance of rho=0.994 and p=0.000; likewise, the stability dimension shows a coefficient and significance of rho=0.990 and p=0.000; finally, the change dimension shows a coefficient and significance of rho=0.993 and p=0.00. These dimensions are directly related to the type of communication in secondary school students.